SRRM2 organizes splicing condensates to regulate alternative splicing - Xu, Shaohai (2023)
SRRM2 is a nuclear-speckle marker containing multiple disordered domains, whose dysfunction is associated with several human diseases. Using mainly EGFP-SRRM2 knock-in HEK293T cells, we show that SRRM2 forms biomolecular condensates satisfying most hallmarks of liquid-liquid phase separation, including spherical shape, dynamic rearrangement, coalescence and concentration dependence supported by in vitro experiments. Live-cell imaging shows that SRRM2 organizes nuclear speckles along the cell cycle. As bona-fide splicing factor present in spliceosome structures, SRRM2 deficiency induces skipping of cassette exons with short introns and weak splice sites, tending to change large protein domains. In THP-1 myeloid-like cells, SRRM2 depletion compromises cell viability, upregulates differentiation markers, and sensitizes cells to anti-leukemia drugs. SRRM2 induces a FES splice isoform that attenuates innate inflammatory responses, and MUC1 isoforms that undergo shedding with oncogenic properties. We conclude that SRRM2 acts as a scaffold to organize nuclear speckles, regulating alternative splicing in innate immunity and cell homeostasis.